Flipped Classroom, Teaching Solution for Writing Class - Nugroho Nugroho; Dwi Rorin M Insana (Scope : Journal of English Language Teaching, 2018)
The research was designed to investigate the result of a study comparing two English writing classes of  Indraprasta PGRI University student in  the sixth semester of 2015/2016. There were thirty students for each class chosen randomly. The research was conducted from March to July 2016. One class was taught in a traditional way and the other using the flipped method. A test is given at the end of the treatment to detect the level of student understanding. Results of post test are  compared using t-test to gauge whether the method of "Flipped Classroom" has effect on student understanding. This research is a field research with posttest-only control group design method. The theoryused to determine the ability of the students is a statistical theory  by Sudjana, cohesion were analyzed using the theory of Cohesion in English by Halliday and Hassan. Factors affect the ability to write theory by Harmer. The study resulted tcount 2,256 and ttable 1.67 at ? = 0.05 level. So tcount> ttable, so that Ho refused mean significant. It can be concluded also that there is a positive and significant influence.